A survey of the commercial traits and antioxidant status of goat milk in Mediterranean pastoral farms - Manuel Delgado-Pertiñez; Juan M. Mancilla-Leytón; Eduardo Morales-Jerrett; Sara Muñoz-Vallés; Verónica Cruz; Yolanda Mena (Spanish Journal of Agricultural Research)
Aim of study: To enhance the viability of goat farms in Mediterranean mountain areas, studies have proposed strategies to improve the marketing of their animal products. The primary aim of this work was to provide an overview of the commercial traits and antioxidant composition of milk produced on Payoya farms. A second aim was to assess the relationships between the antioxidant capacity (TAC) and the hygiene-sanitary parameters in milk.